Impact of Elotuzumab Plus Pomalidomide/Dexamethasone on Health-related Quality of Life for Patients With Relapsed/Refractory Multiple Myeloma: Final Data From the Phase 2 ELOQUENT-3 Trial - Katja Weisel; Meletios A. Dimopoulos; Jesús San-Miguel; Agne Paner; Monika Engelhardt; Fiona Taylor; Jennifer Lord-Bessen; Christine Yip; Mike Greenwood; Jackson Tang; Michele Cavo (HemaSphere, 2023)
Triplet regimens containing immunomodulatory drugs and proteasome inhibitors (PIs) have improved outcomes and extended survival for patients with relapsed/refractory multiple myeloma (RRMM). We evaluated updated health-related quality of life (HRQoL) findings from the phase 2 ELOQUENT-3 clinical trial (NCT02654132) after 4 years of treatment with elotuzumab plus pomalidomide and dexamethasone (EPd) and assessed the impact of the addition of elotuzumab on patients’ HRQoL. HRQoL was assessed as an exploratory endpoint using the MD Anderson Symptom Inventory for Multiple Myeloma (MDASI-MM), which evaluates symptom severity, symptom interference, and HRQoL, and the 3-level EQ-5D, a patient-reported measure of health utility and general health. Statistical analyses included descriptive responder, longitudinal mixed-model, and time-to-first-deterioration (TTD) analyses using prespecified minimally important differences and responder definitions. Of 117 randomized patients, 106 (EPd, n = 55; pomalidomide and dexamethasone [Pd], n = 51) were eligible for inclusion in HRQoL analyses. Completion rates at almost all on-treatment visits were ≥80%. The proportion of patients treated with EPd who improved or maintained stable HRQoL until cycle 13 ranged from 82% to 96% for MDASI-MM total symptom score and 64% to 85% for MDASI-MM symptom interference. Across measurements, there were no clinically meaningful differences in changes from baseline between treatment arms, and TTD was not significantly different for EPd versus Pd. In conclusion, HRQoL was not impacted by the addition of elotuzumab to Pd and did not significantly deteriorate in patients with RRMM previously treated with lenalidomide and a PI in ELOQUENT-3.